2008
DOI: 10.1111/j.1600-0560.2007.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Concordant loss of heterozygosity of DNA repair gene, hOGG1, in melanoma in situ and atypical melanocytic hyperplasia

Abstract: These results shows that LOH at hOGG1 gene is associated with MIS and AMH and suggest that the hOGG1 gene may play a role in melanocytic tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Several potential mechanisms of ROS accumulation in melanomas have been suggested. Loss-of-heterozygosity mutations in hOGG1, an enzyme that repairs oxidative DNA damage, have been demonstrated in a small number of melanomas 70,71 . Additionally, we have found that UVA induces Sestrin2 in melanocytes and melanoma cells, which in turn suppresses antioxidant response factor Nrf2 and increases ROS production 59 .…”
Section: Mechanisms Of Uv-induced Melanomamentioning
confidence: 99%
“…Several potential mechanisms of ROS accumulation in melanomas have been suggested. Loss-of-heterozygosity mutations in hOGG1, an enzyme that repairs oxidative DNA damage, have been demonstrated in a small number of melanomas 70,71 . Additionally, we have found that UVA induces Sestrin2 in melanocytes and melanoma cells, which in turn suppresses antioxidant response factor Nrf2 and increases ROS production 59 .…”
Section: Mechanisms Of Uv-induced Melanomamentioning
confidence: 99%
“…Interestingly, melanocytes isolated from melanoma patients display increased sensitivity to peroxidizing agents that correlates with endogenous antioxidant imbalance (Grammatico et al , 1998), and elevated ROS have been found in melanocytes from dysplastic nevi relative to normal skin of the same individuals (Pavel et al , 2004). In addition, mutation or loss of the enzyme hOGG-1, which repairs mutagenic oxidative DNA lesions (namely 8-oxoguanine, 8-OG), has been associated with melanoma progression (Pashaei et al , 2008; Zyrek-Betts et al , 2008). Recently, we demonstrated a role for UV-induced oxidative stress and damage in an animal model of UV-induced melanoma (Cotter et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the Xiphophorus fish model, the UV action spectrum for melanin-dependent oxidant production is identical to that for melanoma induction (20). In addition, mutation or loss of OGG-1 has been associated with melanoma progression (21, 22). Finally, we recently reported that the antioxidant N -acetylcysteine (NAC) delays tumor development in an animal model of UV-induced melanoma (23).…”
Section: Introductionmentioning
confidence: 99%